Pendidikan Antikorupsi Di SMA Al-Hikmah Kebonsari Surabaya - Ahmad Shofiyuddin (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
This article aims to find out 1) What is the Anti-Corruption Education program in Al Hikmah High School Surabaya. 2) How are the Methods and Strategies in the implementation of Anti-Corruption education in Al Hikmah High School Surabaya. 3) What are the Supporting Factors and Barriers to Anti-Corruption Education in Al Hikmah High School Surabaya. While this type of research is field research, namely research carried out by direct involvement in the field to explore and examine data relating to the Anti-Corruption Education Model in Al Hikmah High School Surabaya. While the approach used in this study is a qualitative approach, namely an approach that emphasizes more on the analysis of deductive and inductive inference processes, and on the analysis of the dynamics of the relationship between observed phenomena, using scientific logic. The results showed that the Anti-Corruption Education Program in Al Hikmah High School Surabaya became a part of character education that was inserted and integrated through al Islam or Islamic Education (PAI) and Citizenship Education (PKn) which has nine (9) main values ​​of two material that is. The ten values ​​consist of: Religious, Honest, Tolerant, Discipline, Hard work, Nationalism, Love of the homeland, Social care, and Responsibility. In the Implementation of Anti-Corruption Education in the learning of Islamic Education and Citizenship Education there are supporting factors and inhibiting factors. Supporting factors include: the personality of each student, and the family, school, and community environment that always makes the situation full of honesty, while the one that inhibits is: lack of student awareness, there are still students whose families are less supportive, environment or student background, ability students 'material understanding and technological progress, negative influences from outside of students' personalities and conditions that compel students to act dishonestly, and too often acts of corruption in the presence of corrupt behavior habits. As for instilling anti-corruption values ​​in classroom learning, the Student Centered Learning (SCL) approach is used, while the strategy used is Inquiry Learning Strategy (SPI) using deliberation / discussion method.